Detection of Virulence (etA, etB and tst) and Antibiotic Resistance (mecA) Genes in Staphylococcus Aureus Strains Isolated from Clinical Samples Using Multiplex-PCR Method - Fatemeh Mohammad Jani; Kumarss Amini (Tehran University of Medical Sciences, 2018)
Background and Aim: Staphylococcus aureus produces many virulence factors, including toxins, immune-modulatory factors, and exoenzymes. The study was performed to determine virulence and resistance-related factors etA, etB, tst, mecA and femA in the S. aureus isolated from clinical samples using Multiplex PCR. Materials and Methods: In this cross - sectional study, a total 60 S. aureus were collected from the Shariati hospital in Tehran, Iran. Susceptibility test to several antimicrobial agents was performed by disk diffusion agar based on clinical and laboratory standard institute guidelines. After DNA extraction, the multiplex-PCR amplification of the etA, etB, tst, mecA and femA was performed in all the clinical isolates.  Results: In this study, all isolates (100%) were positive for the presence of femA gene. The highest and lowest resistance rate were related to erythromycin and cefoxitin, respectively. 33.3% (n; 20) and 43.3% (n; 26) of isolates carried in order etb and tst genes. All strains were negative for the eta gene. Conclusion: Our results showed that, among many virulence factors produced by S. aureus, etb, tst play an important role in the pathogenesis of staphylococcal infections. Results suggested that identification of MRSA strains to be done using cefoxitin disk (in comparison of oxacillin) or PCR for mecA gene.